PPARβ/δ agonism upregulates forkhead box A2 to reduce inflammation in C2C12 myoblasts and in skeletal muscle - Phua, Wendy Wen Ting (2020)
Daily activities expose muscles to innumerable impacts, causing accumulated tissue damage and inflammation that impairs muscle recovery and function, yet the mechanism modulating the inflammatory response in muscles remains unclear. Our study suggests that Forkhead box A2 (FoxA2), a pioneer transcription factor, has a predominant role in the inflammatory response during skeletal muscle injury. FoxA2 expression in skeletal muscle is upregulated by fatty acids and peroxisome proliferator-activated receptors (PPARs) but is refractory to insulin and glucocorticoids. Using PPARβ/δ agonist GW501516 upregulates FoxA2, which in turn, attenuates the production of proinflammatory cytokines and reduces the infiltration of CD45+ immune cells in two mouse models of muscle inflammation, systemic LPS and intramuscular injection of carrageenan, which mimic localized exercise-induced inflammation. This reduced local inflammatory response limits tissue damage and restores muscle tetanic contraction. In line with these results, a deficiency in either PPARβ/δ or FoxA2 diminishes the action of the PPARβ/δ agonist GW501516 to suppress an aggravated inflammatory response. Our study suggests that FoxA2 in skeletal muscle helps maintain homeostasis, acting as a gatekeeper to maintain key inflammation parameters at the desired level upon injury. Therefore, it is conceivable that certain myositis disorders or other forms of painful musculoskeletal diseases may benefit from approaches that increase FoxA2 activity in skeletal muscle.